Variation in sources of inorganic nitrogen under different hydrological conditions in a floodplain lake: a case study of Bang Lake (Poyang Lake, Jiangxi Province, China). Issue 2 (3rd April 2018) - Liang, Yue; Xiao, Huayun; Liu, Xiaozhen; Hu, Qianqian; Xiong, Jian; Li, Wenhua; Tang, Congguo
ABSTRACT: Bang Lake, a shallow floodplain lake in Jiangxi Province, China, is a complex environment with water levels and sources of pollutants that vary considerably on an annual scale. We collected rain and water samples from the lake and around connecting rivers through lentic, flowing, flooding, and lowering level periods. We distinguished sources of dissolved inorganic nitrogen (DIN as ammonium NH4 + and nitrate NO3 − ) in the lake from δ 15 N. Stable isotopes of hydrogen (δD), oxygen (δ 18 O), and δ 15 N (δ 15 NH4 +, δ 15 NO3 − ) in water samples were used to describe lake–river water exchanges and DIN sources at different water levels in the floodplain lake. The sources of DIN varied through the different hydrological stages in the lake. In the lentic periods, δ 18 O and δD values were more positive and δ 15 N (δ 15 NH4 +, δ 15 NO3 − ) values were more negative in lake water than in river water and rainwater, indicating lake–river separation. During the flowing period, δ 18 O, δD, and δ 15 N values in river and lake water were similar, and DIN mainly derived from agriculture and livestock wastewater. During the flooding period, δ 15 N values in the lake and rivers differed even though they were connected at the highest water levels. When the water levels were declining, considerable variation was measured for δ 15 NH4 + or δ 15 NO3 − signatures between the lake and river water as the lake and river water gradually separated. The significant increase of δ 15 NH4 + and decrease of δ 15 NO3 − indicated strong ammonification and nitrification in the lake.